2023
DOI: 10.3390/microorganisms11051184
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome of Ceca from Broiler Chicken Vaccinated or Not against Coccidiosis and Fed Berry Pomaces

Abstract: American cranberry (Vaccinium macrocarpon) and lowbush/wild blueberry (V. angustifolium) pomace are polyphenol-rich products having potentially beneficial effects in broiler chickens. This study investigated the cecal microbiome of broiler-vaccinated or non-vaccinated birds against coccidiosis. Birds in each of the two groups (vaccinated or non-vaccinated) were fed a basal non-supplemented diet (NC), a basal diet supplemented with bacitracin (BAC), American cranberry (CP), and lowbush blueberry (BP) pomace alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…In our study, to characterize the overall function of the cecal community, we mapped the identified metabolites to the E. coli to represent the pathways associated with the microbial community in poultry ceca. E. coli is widely studied as a prokaryotic model organism and plays a significant role in the cecal community, closely linked to Campylobacter colonization [47][48][49]. Our study has unveiled disparities in protein order of structure and molecular size, indicating differences among the core microbiota and the abundance of vitamin B-associated metabolites.…”
Section: Plos Onementioning
confidence: 77%
“…In our study, to characterize the overall function of the cecal community, we mapped the identified metabolites to the E. coli to represent the pathways associated with the microbial community in poultry ceca. E. coli is widely studied as a prokaryotic model organism and plays a significant role in the cecal community, closely linked to Campylobacter colonization [47][48][49]. Our study has unveiled disparities in protein order of structure and molecular size, indicating differences among the core microbiota and the abundance of vitamin B-associated metabolites.…”
Section: Plos Onementioning
confidence: 77%
“…Therefore, nutritional approaches that support immune system development and mitigate the negative effects on growth performance, while also combating infection, are promising. Phytogenic feed additives are, next to probiotics, the most frequently tested alternatives to standard programs against coccidiosis [ 16 , 17 , 18 , 19 , 20 , 57 ]. T. officinale could be considered a medicinal plant due to its rich content of bioactive substances, which have demonstrated broad pharmacological properties in both in vitro and in vivo studies [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of these challenges, there is a growing interest in exploring natural methods that can support coccidiosis immunoprophylaxis and improve the overall health and productivity of vaccinated broiler chickens. One promising strategy is the use of plant extracts in poultry nutrition as they serve as a rich source of diverse bioactive substances capable of exerting their beneficial effects through various mechanisms of action [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%